The bZIP transcription factors in Liriodendron chinense: Genome-wide recognition, characteristics and cold stress response - Li, Mingyue; Hwarari, Delight; Li, Yang; Ahmad, Baseer; Min, Tian; Zhang, Wenting; Wang, Jinyan; Yang, Liming (Frontiers in Plant Science, 2022)
The basic leucine zipper (bZIP) is a transcription factor family that plays critical roles in abiotic and biotic stress responses as well as plant development and growth. A comprehensive genome-wide study in Liriodendron chinese was conducted to identify 45 bZIP transcription factors (LchibZIPs), which were divided into 13 subgroups according the phylogenetic analysis. Proteins in the same subgroup shared similar gene structures and conserved domains, and a total of 20 conserved motifs were revealed in LchibZIP proteins. Gene localization analysis revealed that LchibZIP genes were unequally distributed across 16 chromosomes, and that 4 pairs of tandem and 9 segmental gene duplications existed. Concluding that segmental duplication events may be strongly associated with the amplification of the L. chinense bZIP gene family. We also assessed the collinearity of LchibZIPs between the Arabidopsis and Oryza and showed that the LchibZIP is evolutionarily closer to O. sativa as compared to the A. thaliana. The cis-regulatory element analysis showed that LchibZIPs clustered in one subfamily are involved in several functions. In addition, we gathered novel research suggestions for further exploration of the new roles of LchibZIPs from protein-protein interactions and gene ontology annotations of the LchibZIP proteins. Using the RNA-seq data and qRT-PCR we analysed the gene expression patterns of LchibZIP genes, and showed that LchibZIP genes regulate cold stress, especially LchibZIP4 and LchibZIP7; and LchibZIP2 and LchibZIP28 which were up-regulated and down-regulated by cold stress, respectively. Studies of genetic engineering and gene function in L. chinense can benefit greatly from the thorough investigation and characterization of the L. chinense bZIP gene family.